2018
DOI: 10.1111/apa.14408
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural streptokinase is effective and safe for children with multi‐loculated empyema regardless of the time from disease onset

Abstract: Intrapleural streptokinase was effective for multi-loculated empyema even when it was administered more than 14 days after disease onset and four to six doses were superior to three doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Children in this study had symptoms for 2-3 wk prior to presentation. Although it does not suggest that empyema was present for the same duration, it indirectly confirms our findings that fibrinolytics can work even beyond the traditional time limit of 7-10 d [8]. Unfortunately, more careful analysis of the duration is hampered because the authors presented data using medians (in the tables) and means (in the text).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Children in this study had symptoms for 2-3 wk prior to presentation. Although it does not suggest that empyema was present for the same duration, it indirectly confirms our findings that fibrinolytics can work even beyond the traditional time limit of 7-10 d [8]. Unfortunately, more careful analysis of the duration is hampered because the authors presented data using medians (in the tables) and means (in the text).…”
supporting
confidence: 69%
“…The authors also did not describe the criteria for removal of chest tube drains, definition of treatment failure, criteria for surgical referral, time lag between referral and surgery, postsurgical morbidity & hospitalization, etc. We have previously observed that children undergoing surgery have longer duration of hospitalization and intercostal drainage [8]. In this study, it is unclear whether the statistically significant and clinically impressive differences (in the mean durations of hospitalization and intercostal drainage) were because 9/44 (20.5%) children in the non-urokinase group underwent surgery, compared to 4/10 (10%) among those who received it.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Use of nonoperative alternatives is connected with increased morbidity and mortality [21]. Fibrinolysis is seldom a one-stage procedure [22]. A nationwide surveillance study from Germany revealed that a third of those initially treated with noninvasive therapy required secondary, invasive treatment [23].…”
Section: Discussionmentioning
confidence: 99%
“…The drainage effusion amount should be monitored and recorded daily, with recommended therapy ranging from 3 to 5 days. The success rate with streptokinase is 70%-90%, usually in three doses but up to 6 doses can be helpful [86][87][88][89][90].…”
Section: Ct+ Fibrinolysismentioning
confidence: 99%